2020
DOI: 10.3775/jie.99.123
|View full text |Cite
|
Sign up to set email alerts
|

Development of De-Oiled Cashew Nut Shell as Fuel Briquettes

Abstract: Converting the de-oiled cashew nut shell into usable products (e.g. briquettes) will address the problem of waste disposal. The study was conducted to develop an environment-friendly fuel briquette sufficient to resist impact during handling and transport and produce the required heat for domestic cooking and also for industrial application. Piston-type and screw-type briquetting machines and three levels of binding agent were used in the production of de-oiled spent cashew shell-based fuel briquettes. The pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…On average, these shells are dried under sun between 1 and 4 days; and are very effective in bringing down their moisture content below 10% with minimal energy and cost (Ifa et al, 2020;Kimutai, 2021). Likewise, even de-oiled and solvent treated CNS also report upto 13% of moisture content, and needs to be sun dried for 3 to 5 days in order to reduce it below 7% (Tuates Jr et al, 2020). In fact, even briquettes are also dried in similar manner; and supporting this, Sawekwiharee et al (2015) reported the average weight of the sun dried CNS briquettes, with dimension of 5×4.5 cm as 42.49 g (Sawekwiharee et al, 2015).…”
Section: Drying Of Cns Wastesmentioning
confidence: 99%
See 4 more Smart Citations
“…On average, these shells are dried under sun between 1 and 4 days; and are very effective in bringing down their moisture content below 10% with minimal energy and cost (Ifa et al, 2020;Kimutai, 2021). Likewise, even de-oiled and solvent treated CNS also report upto 13% of moisture content, and needs to be sun dried for 3 to 5 days in order to reduce it below 7% (Tuates Jr et al, 2020). In fact, even briquettes are also dried in similar manner; and supporting this, Sawekwiharee et al (2015) reported the average weight of the sun dried CNS briquettes, with dimension of 5×4.5 cm as 42.49 g (Sawekwiharee et al, 2015).…”
Section: Drying Of Cns Wastesmentioning
confidence: 99%
“…Other works include burning of CNS (1 kg) in muffle furnace at 600 ⁰C for 60 minutes; burning in open air for 75 minutes, followed by closed combustion in absence of oxygen for another 30 minutes (Sawekwiharee et al, 2015), burning in developed prototype kiln (capacity of 5 kg) using direct carbonization at 452.2 ⁰C, and indirect carbonization at 458.8 ⁰C (Sanger et al, 2011). Besides, these shells can also be carbonized in customised metal box, maintained at 250 °C for 3 hours (Sen et al, 2016;Sanger et al, 2011); and a drum type carbonizer operated at 250-350 °C (Tuates Jr et al, 2020). Eventually, carbonizing these wastes into biochar enhances their overall combustion efficiency and eases the briquetting process (Sanger et al, 2011).…”
Section: Pyrolysis and Carbonizing Of Cns Wastesmentioning
confidence: 99%
See 3 more Smart Citations